MODELLING OF HOUSEHOLD FINANCIAL BEHAVIOUR - Сидорчук, Анатолій (Modern engineering and innovative technologies, 2023)
The article discusses the modelling of household financial behaviour. Synthesis and analysis are used as a general scientific method of scientific cognition. The purpose of the study is to consider possible stages of modelling households’ financial behav